Antioxidant properties of different blueberries species - Hryvnak, B.; Baranovsky, M. (Problems of Environmental Biotechnology, 2018)
Nowadays antioxidant properties of blueberries are widely used in medicine for drugs production and as additives to cosmetic products. Those fruits contain in composition different phenolic compounds, which eventually ensure their antioxidant properties. The number of blueberry plantations is increasing on the territory of Ukraine; therefore, the study of the antioxidant properties of various types of blueberry is particularly relevant. For recommendations on the production of commercial blueberries species, it is essential to determine the content of biologically active substances and evaluate their antioxidant activity of potentially useful parts of the plant.